Identification of target system operations. Determination of the time of the actual completion of the target operation - Lutsenko, Igor (Eastern-European Journal of Enterprise Technologies, 2014)
It was found in the paper that the time frames of the studied system operation depend on the research objective. In cases when it comes to problems, related to the physical movement of the input and output products, limits of the study are defined by the time of the beginning of the movement of the first input product of the operation and ends with the time of issue of the last output product of the operation by the system. Time of completion of the physical movement of products is defined in the paper as the time of the physical completion of the operation. Since the purpose of any operation is to increase the value of the output products in relation to the value of input products of the operation, in cases when there is a problem of investigating the target operation, the time of completion of the target operation is determined not by the physics of the process, but its cybernetics. Since for the time of the operation, conversion processes link input products in time, the added value of output products is intended to compensate in time the costs of temporary binding of input products that initially have their value. The time, when the added value of output products of the target operation compensates the value of tight input products for the time of the operation, is defined in the paper as the time of the actual completion of the target operation. A system of notations to describe the system processes of target operations was proposed. The expressions for the numerical and analytical determination of the time of actual completion of the target operation were obtained. A link to the resource, with examples of calculations of the time of the actual completion of the operation with the use of numerical methods and analytic expressions, obtained in the paper was given.